Refining rather than redefining the BVS in "real world". Issue 6 (15th November 2015) - Seth, Ashok; Ezhumalai, Babu
Key Points: The article outlines the factors influencing acute recoil of BVS after implantation, especially the role of lesion preparation and predilatation. It attracts attention to "optimal implantation technique" of BVS in complex "real world" patients to improve outcomes and avoid scaffold thrombosis. Large multicenter registries/trials in complex lesions utilizing "optimal implantation techniques" could establish the role of BVS in our "real world" practice.